ANALISIS KEBUTUHAN BANGSAL DAN PENGARUHNYA TERHADAP EFISIENSI TENAGA KERJA DAN PENDAPATAN PENGRAJIN GULA AREN DI KECAMATAN PINING KABUPATEN GAYO LUWES - Elly Susanti; Indra Indra; Menti Mentari (Jurnal Bisnis Tani, 2018)
This research was aimed at determining the number of sheds required by palm sugar craftsmen and the contribution of making them to the efficiency of labors and the income level of palm sugar craftsmen in Pining Sub-district, Gayo Lues Regency. The result of the research showed that the palm sugar craftsmen in Pining Sub-district, Gayo Regency required 5 unit sheds. From the calculation result by doing multiple linear regression analysis, it was got the level of efficiency in the use of the labors before existing the sheds was < 1 namely 0.05. It showed that the use of the labors was not efficient, then the level efficiency of the use of the labor was > 1 namely 1.81. It indicated that the rate of the labors was almost efficient and could be added again so that it became efficient. The average income of the craftsmen was higher if there were the sheds namely in the amount of Rp.926. 444, - than if there were no the sheds namely only in the amount of Rp 383. 968, -.